Investigation of sub-acute levels of zinc oxide nanoparticles on the filtration rate of Mytilaster lineatus and Dressina polymorpha in the short term - AMIR QADERMARZI; MOJTABA POULADI; ALI REZAMAND; SEYED HOSSEIN HOSEINIFAR; ALI AKBAR HEDAYATI (Nusantara Bioscience, 2018)
Qadermarzi A, Pouladi M, Rezamand A, Hoseinifar SH, Hedayati AA. 2018. Investigation of sub-acute levels of zinc oxide nanoparticles on the filtration rate of Mytilaster lineatus and Dressina polymorpha in the short term. Nusantara Bioscience 10: 53-57. The filtration rate is one of the physiological indices in the bivalves which indicate the degree of efficacy of the filtration function in the exposure to contaminants. In this study, changes in the filtration rate of freshwater bivalves (D. polymorpha and M. lineatus) were investigated after exposure periods of 5 and 10 days with nanoparticles. Bivalves were transferred from the natural environment to the laboratory. The distribution of nanoparticles was measured by differential light scattering (DLS). Bivalves were exposed to 2.5, 25 and 50 ppm nanoparticles for ten days in water reservoirs. The filtration rates were significantly different in the treatments compared to the control samples, with the highest filtration rate was observed in the control group. On the fifth day, the highest filtration rate was obtained in the first treatment of M. lineatus and the lowest filtration rate was obtained in the third treatment of D. polymorphia. The highest filtration rates were observed in the first and second treatments and the lowest filtration rate was observed in the third treatment. Also, there was no significant difference in the filtration rate of M. lineatus in the 1st treatment with control (P> 0.05) on the 5th day, but filtration rate was significantly (P <0.05) less than other concentrations and control group in the third treatment. On the other hand, the filtration rates on the 10th day showed similar differences compared to the 5th day. It could be concluded that the changes infiltration rate are an appropriate indicator for the measurement of contamination in nanoparticles.